Leisure education, community development, and populations with special needs - Sivan, A.; Ruskin, H. (United Kingdom CABI Publishing, 2000)
This book is a result of an output of Commission of the World Leisure and Recreation Association (WLRA) to examine the role of leisure and education for leisure activities among people with special needs living in the community, requiring social or health services outside hospital. This book provides a conceptual and practical framework for understanding the process of leisure education and its role for community development and populations with special needs. It will serve the reader as a foundation for developing models and programmes for leisure education within community settings and will be of interest to those working and researching in the area of education, leisure and community development
1. Educating the community for developmental opportunities in leisure -- 2. Leisure education, serious leisure and community development -- 3. Community development through leisure education: conceptual approaches -- 4. Leisure education, quality of life and community development: toward a systematic and holistic coping and resilient model for the third millennium -- 5. Mobility for action: advocacy and empowerment for the right of leisure, play and recreation -- 6. Global edutainment: the role of leisure education for community development -- 7. Community vision and resources: commitment, capacity and collective effort -- 8. Leisure opportunities for persons with disabilities -- 9. The role of leisure counselling for special populations in facilitating successful adjustment to life in the community -- 10. Serious leisure for people with disabilities -- 11. Leisure education, quality of life and populations with special needs -- 12. Active living for people with disabilities: toward the concept of equality of well-being and human existentialism (Authenticity) 13. Community empowerment, poverty and leisure education -- 14. Establishing a multi-purpose model for the rehabilitation of children with special needs
Includes bibliographical references and index
Keywords: Leisure -- Study and teaching -- Congresses; Community development -- Congresses; Handicapped -- Recreation -- Congresses